Exploring the Potential of Lactobacillus helveticus R0052 and Bifidobacterium longum R0175 as Promising Psychobiotics Using SHIME - De Oliveira, Fellipe Lopes [UNESP]; Salgaço, Mateus Kawata [UNESP]; de Oliveira, Marina Toscano; Mesa, Victoria; Sartoratto, Adilson; Peregrino, Antonio Medeiros; Ramos, Williams Santos; Sivieri, Katia [UNESP] (MDPI, 2023)
Psychobiotics are probiotics that have the characteristics of modulating central nervous system (CNS) functions or reconciled actions by the gut–brain axis (GBA) through neural, humoral and metabolic pathways to improve gastrointestinal activity as well as anxiolytic and even antidepressant abilities. The aim of this work was to evaluate the effect of Lactobacillus helveticus R0052 and Bifidobacterium longum R0175 on the gut microbiota of mildly anxious adults using SHIME®. The protocol included a one-week control period and two weeks of treatment with L. helveticus R0052 and B. longum R0175. Ammonia (NH4+), short chain fatty acids (SCFAs), gamma-aminobutyric acid (GABA), cytokines and microbiota composition were determined. Probiotic strains decreased significantly throughout the gastric phase. The highest survival rates were exhibited by L. helveticus R0052 (81.58%; 77.22%) after the gastric and intestinal phase when compared to B. longum (68.80%; 64.64%). At the genus level, a taxonomic assignment performed in the ascending colon in the SHIME® model showed that probiotics (7 and 14 days) significantly (p < 0.005) increased the abundance of Lactobacillus and Olsenella and significantly decreased Lachnospira and Escheria-Shigella. The probiotic treatment (7 and 14 days) decreased (p < 0.001) NH4+ production when compared to the control period. For SCFAs, we observed after probiotic treatment (14 days) an increase (p < 0.001) in acetic acid production and total SCFAs when compared to the control period. Probiotic treatment increased (p < 0.001) the secretion of anti-inflammatory (IL-6 and IL-10) and decreased (p < 0.001) pro-inflammatory cytokines (TNF-alpha) when compared to the control period. The gut–brain axis plays an important role in the gut microbiota, producing SCFAs and GABA, stimulating the production of anti-anxiety homeostasis. The signature of the microbiota in anxiety disorders provides a promising direction for the prevention of mental illness and opens a new perspective for using the psychobiotic as a main actor of therapeutic targets.
Keywords: colonic fermentation; microbiota–brain-axis; psychobiotic